Performance of serological tests PGL1 and NDO-LID in the diagnosis of leprosy in a reference Center in Brazil - André Luiz Leturiondo; Ariani Batista Noronha; Monik Oney Oliveira do Nascimento; Cynthia de Oliveira Ferreira; Fabíola da Costa Rodrigues; Milton Ozório Moraes; Carolina Talhari (BMC Infectious Diseases, 2019)
Abstract Background Early detection of leprosy and multidrug therapy are crucial to achieve zero transmission and zero grade II incapacities goals of World Health Organization. Leprosy is difficult to diagnose because clinical forms vary and there are no gold standard methods to guide clinicians. The serological rapid tests aid the clinical diagnosis and are available for field use. They are easy to perform, do not require special equipment or refrigeration and are cheaper than the molecular tests. Methods We evaluated the performance of two rapid serological tests (PGL1 and NDO-LID) in the discrimination of leprosy cases from healthy individuals at the Alfredo da Matta Foundation, a reference center for the disease in Manaus, Amazonas, Brazil. PGL1 and NDO-LID rapid tests are capable of detecting specific antibodies of M. leprae, IgM and IgM/IgG, respectively. A total of 530 healthy subjects and 171 patients (50 with paucibacillary and 121 multibacillary leprosy) were included in the study. Results Among the paucibacillary leprosy patients, the sensitivity was 34.0 and 32.0% for the NDO-LID and PGL1, respectively. In multibacillary leprosy patients, the NDO-LID sensitivity was 73.6% and the PGL1 was 81.0%. Serological tests demonstrated specificities of 75.9% for PGL-1 and 81.7% for NDO-LID. The positive predictive value (PPV), negative predictive value (NPV) and accuracy in multibacillary patients were 47.9, 93.1, and 80.2% respectively for the NDO-LID, and 43.4, 94.6 76.8% for PGL1. Conclusions The tests showed limited capacity in the diagnosis of the disease, however, the high negative predictive value of the tests indicates a greater chance of true negatives in this group favoring exclusion of leprosy. This characteristic of the ML flow test is important in aiding clinical Diagnosis, especially in a region endemic to the disease and with other confounding skin conditions.